2019
DOI: 10.1155/2019/5160565
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of TIGIT Expression in Lymphatic Tissue, Inflammation, and Cancer

Abstract: TIGIT is an inhibitory immune checkpoint receptor and a putative target for novel immune therapies. Here, we analysed two different types of tissue microarrays of healthy lymphatic and various inflamed tissues, colorectal and lung cancers, as well as >1700 tumour samples from 86 different tumour entities for TIGIT and/or PD-1 by bright field and/or multiplex fluorescence immunohistochemistry. TIGIT was detected in CD8+ cytotoxic T cells, CD4+ T helper cells, FOXP3+ regulatory T cells, and NK cells, but not in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…TIGIT is highly expressed on NK cells, CD8 + T cells and Treg cells within the TME. [188][189][190][191] Its ligands CD155 and CD112 are widely expressed on tumor cells. [192][193][194] Multiple studies showed that TIGIT signaling is involved in dampening both T-cell activation and differentiation into anti-tumor effector cells.…”
Section: T-cell Exhaustion In Cancermentioning
confidence: 99%
“…TIGIT is highly expressed on NK cells, CD8 + T cells and Treg cells within the TME. [188][189][190][191] Its ligands CD155 and CD112 are widely expressed on tumor cells. [192][193][194] Multiple studies showed that TIGIT signaling is involved in dampening both T-cell activation and differentiation into anti-tumor effector cells.…”
Section: T-cell Exhaustion In Cancermentioning
confidence: 99%
“…Recently, interest in other immune checkpoints has intensified and novel potential targets have been identified such as TIM-3, LAG-3, TIGIT, or VISTA. Expressed on activated T cells and NK cells among others, these receptors have been found highly expressed on TILs as compared to circulating T cells in CRC patients (127)(128)(129)(130). As with PD-1 or CTLA-4, physiologically, these inhibitory receptors are induced following the activation of T cells to prevent overstimulation, which may result in an exhausted state.…”
Section: Future Alternatives: New Generation Of Immune Checkpoint Inhmentioning
confidence: 99%
“…This was expected because in an earlier study using a comparable experimental set-up, we had also regularly found TIGIT expression in a considerable fraction of lymphocytic cells in healthy lymphatic organs, various inflammatory diseases and in samples of lung and colorectal cancers (19). Taken together, these findings strongly support the concept that TIGIT expression is an inherent feature of T cell lymphocytic infiltrations in normal, inflammatory and cancerous tissues (19). Earlier studies using flow cytometry have also described regular presence of TIGIT + T cells in these immune microenvironments (13,17,21,24,25).…”
Section: Discussionmentioning
confidence: 52%
“…T cell immunoreceptor with Ig and ITIM domain (TIGIT), a co-inhibitory transmembrane glycoprotein of the poliovirus receptor (PVR)/nectin superfamily, is another interesting candidate for novel checkpoint therapies (13,14). In mouse models and ongoing clinical studies, blockade or ablation of TIGIT, alone or in combination with blockade of PD-1, can restore tumor suppressive effects (1519). These findings indicate that TIGIT, similar to PD-1, has a crucial role in inhibiting the tumor-directed immune response and, thus, might be a suitable and relevant target for novel immune-modulating therapies.…”
Section: Introductionmentioning
confidence: 99%